The Effectiveness of the Discovery Learning Model with a Scientific Approach to the Learning Outcomes of Mathematics Students of Class VII of Al-Azhar Paron Middle School - Inayatul Husniyah; Arum Dwi Rahmawati; Budi Sasomo (Institute of Educational, Research, and Community Service, 2024)
This research was conducted at Al-Azhar Paron Middle School with the aim of finding out whether the discovery learning model with a scientific approach was more effective than conventional learning models on the mathematics learning outcomes of class VII students at Al-Azhar Paron Middle School. The research used is Quasi Experimental research with a Nonequivalent Control Group Design which consists of two research groups, namely an experimental class with a Discovery Learning learning model with a scientific approach and a control class with a conventional learning model. The population in this study were class VII students at Al-Azhar Paron Ngawi Middle School. The research sample was taken using a saturated sampling technique (sample determination when all members of the population are used as samples). The prerequisite test carried out was a normality test using the Lilliefors method and a homogeneity test was carried out to see the similarity of the variants in the two groups. Data were analyzed univariately with a significance level of 5% (0.05) for hypothesis testing using the t-test. The results of the research show that the learning outcomes of students who use the discovery learning model with a scientific approach compared to the conventional learning model are more effectively applied in class VII of Al-Azhar Middle School. The results of calculations using the t test obtained t_count = 2.892 while t_(table )= 2.042, which shows that t_count > t_table at a significance level of 5% (0.05), meaning that H_0 is rejected, giving us confidence that the research hypothesis is accepted. These results can then be interpreted to mean that the application of the discovery learning model with a scientific approach is more effective than the conventional learning model on mathematics learning outcomes in class VII Al-Azhar Paron Middle School.